Essays on credit default swaps - Guo, Biao (2013)
This thesis is structured to research on a financial derivative asset known as a credit default swap (CDS). A CDS is a contract in which the buyer of protection makes a series of payments (often referred to as CDS spreads) to the protection seller and, in exchange, receives a payoff if a default event occurs. A default event can be defined in several ways, including failure to pay, restructuring or rescheduling of debt, credit event repudiation, moratorium and acceleration.